Silence [videorecording (DVD)] - Scorsese, Martin; Garfield, Andrew, 1983-; Driver, Adam; Neeson, Liam; Endō, Shūsaku, 1923-1996 (Paramount, 2017)
Two Catholic missionaries face the ultimate test of faith when they travel to Japan looking for their missing mentor, at a time when Catholicism was outlawed.